2021
DOI: 10.3390/jcm10071336
|View full text |Cite
|
Sign up to set email alerts
|

The Long-Term Follow-Up of Patients with Cystine Stones: A Single-Center Experience for 13 Years

Abstract: Introduction: Cystine stone development is relatively uncommon among patients with urolithiasis, and most studies have reported only on small sample sizes and short follow-up periods. We evaluated clinical courses and treatment outcomes of patients with cystine stones with long-term follow-up at our center. Methods: We retrospectively analyzed 22 patients diagnosed with cystine stones between January 1989 and May 2019. Results: The median follow-up was 160 (range 6–340) months, and the median patient age at di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Primary intervention was four SWL cases, five URS cases, and 13 PNL cases but the most patients were adults (median age: 46 years, range: 12-82 years). 5 Inoue et al reported about bilateral cystine stones of 2-year-old boy successfully treated by super ultra-mini endoscopic renal surgery (sheath 8.5/9.5Fr). 6 Currently, miniaturized nephroscopy and URS, improvement of laser technology and fine retrieval instruments have revolutionized minimally invasive surgery in children.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Primary intervention was four SWL cases, five URS cases, and 13 PNL cases but the most patients were adults (median age: 46 years, range: 12-82 years). 5 Inoue et al reported about bilateral cystine stones of 2-year-old boy successfully treated by super ultra-mini endoscopic renal surgery (sheath 8.5/9.5Fr). 6 Currently, miniaturized nephroscopy and URS, improvement of laser technology and fine retrieval instruments have revolutionized minimally invasive surgery in children.…”
Section: Discussionmentioning
confidence: 99%
“…reported about 22 cases of long‐term follow‐up (median 160 months). Primary intervention was four SWL cases, five URS cases, and 13 PNL cases but the most patients were adults (median age: 46 years, range: 12–82 years) 5 . Inoue et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the number of new stone occurrences, spontaneous stone expulsions, renal colic, hematuria due to lithiasis, acute pyelonephritis, hospital admissions due to lithiasis, and surgical intervention to remove the lithiasis were grouped into a single numerical variable called lithiasis events. The number of lithiasis events for each patient was normalized by years of follow-up, as other authors have proceeded [31,32]. Urinary excretion of cystine, lysine, ornithine, and arginine, and where possible, aspartate and glutamate were also acquired.…”
Section: Patientsmentioning
confidence: 99%
“…Cystine stones commonly occur bilaterally in 67-73% of cases. 29,30 Bilateral same-sitting ureteroscopy can be undertaken in the management of bilateral urolithiasis, and this is associated with an initial stone-free rate of 87%. 45 Complication rates reported were 50%, although three-quarters of these were Clavien 1 complications.…”
Section: Dovepressmentioning
confidence: 99%